Active Cycle Breathing Technique for Ineffective Airway Clearance in a COPD Patient:ACase Study - Erik Kusuma (Health Gate, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disease that commonly causes ineffective airway clearance due to excessive mucus production and sputum retention. Active Cycle Breathing Technique (ACBT) is a breathing exercise used to facilitate secretion mobilization and improve airway clearance. Objective: This study aimed to describe the implementation of ACBT in a patient with ineffective airway clearance associated with COPD. Methods: A descriptive case study design was used involving one COPD patient hospitalized in Melati Ward, Bangil Regional Hospital. The intervention consisted of breathing control, thoracic expansion exercises, and forced expiration techniques administered once daily for three consecutive days. Clinical indicators observed included respiratory rate, oxygen saturation, cough effectiveness, dyspnea, breath sounds, and sputum characteristics. Results: The results showed progressive improvement during the intervention period. Respiratory rate decreased from 25 to 20 breaths/minute, oxygen saturation increased from 98% to 99%, dyspnea resolved, cough effectiveness improved, and sputum became thinner and easier to expectorate. Conclusion: These findings indicate that Active Cycle Breathing Technique contributed to improved airway clearance and respiratory status. ACBT can be recommended as a complementary nursing intervention for patients with ineffective airway clearance due to COPD.